Structures of an RNA Polymerase Promoter Melting Intermediate Elucidate DNA Unwinding - Boyaci, Hande (Nature, 2019)
A key regulated step of transcription in all cellular organisms is promoter melting by the RNA polymerase (RNAP) to form the open promoter complex(1–3). To generate the open complex, the conserved catalytic core of the RNAP combines with initiation factors to locate promoter DNA, unwind 12–14 base pairs (bps) of the DNA duplex, and load the template-strand (t-strand) DNA into the RNAP active site. Formation of the open complex is a multi-step process with transient intermediates of unknown structures(4–6). Here, we present cryo-electron microscopy structures of bacterial RNAP-promoter DNA complexes, including the first structures of partially melted intermediates. The structures unequivocally show that late steps of promoter melting occur within the RNAP cleft, delineate key roles for fork-loop 2 (FL2) and switch 2 (Sw2), universal structural features of RNAP, in restricting access of DNA to the RNAP active site, and explain why clamp opening is required to allow entry of single-stranded template DNA into the active site. The key roles of the FL2 and Sw2 suggest a common mechanism for late steps in promoter DNA opening to enable gene expression in all domains of life.